Le rôle pédagogique du théâtre dans la formation des enseignants - Miguel F. Gil Palacios (Recherches)
In earlier centuries, when a speaker had trouble speaking in public, theatrical acting was recommended. Currently the same is recommended when children, youths and adults have this type of problem. In these pages we will try to find out why acting can help us to be better communicators and better teachers. To do this, we will base ourselves on the results of two case studies, two research projects that we carried out at the University of Malaga, Spain, in 2012, and at Anne Frank College, Roubaix, in 2003.